Spatial and temporal performance of 3D optical surface imaging for real-time head position tracking - Wiersma, Rodney D.; Tomarken, S. L.; Grelewicz, Zachary; Belcher, Andrew H.; Kang, Hyejoo (Medical physics (Lancaster), 2013)
Purpose: The spatial and temporal tracking performance of a commercially available 3D optical surface imaging system is evaluated for its potential use in frameless stereotactic radiosurgery head tracking applications. Methods: Both 3D surface and infrared (IR) marker tracking were performed simultaneously on a head phantom mounted on anxyz motion stage and on four human subjects. To allow spatial and temporal comparison on human subjects, three points were simultaneously monitored, including the upper facial region (3D surface), a dental plate (IR markers), and upper forehead (IR markers). Results: For both static and dynamic phantom studies, the 3D surface tracker was found to have a root mean squared error (RMSE) of approximately 0.30 mm for region-of-interest (ROI) surface sizes greater than 1000 vertex points. Although, the processing period (1/fps) of the 3D surface system was found to linearly increase as a function of the number of ROI vertex points, the tracking accuracy was found to be independent of ROI size provided that the ROI was sufficiently large and contained features for registration. For human subjects, the RMSE between 3D surface tracking and IR marker tracking modalities was 0.22 mm left-right (x-axis), 0.44 mm superior-inferior (y-axis), 0.27 mm anterior-posterior (z-axis), 0.29° pitch (around x-axis), 0.18° roll (around y-axis), and 0.15° yaw (around z-axis). Conclusions: 3D surface imaging has the potential to provide submillimeter level head motion tracking. This is provided that a highly accurate camera-to-LINAC frame of reference calibration can be performed and that the reference ROI is of sufficient size and contains suitable surface features for registration.